The Consumption Tax Alternative - DAVE DURENBERGER (Tufts Archival Research Center, 2007)
Sen. Dave Durenberger's remarks on the consumption tax alternative. Asserts that a consumption tax would not have a large negative impact. Discourages futher income tax reform or the addition of a surtax. Identifies consumption tax as the only viable alternative to these taxes. Suggests starting at a low rate. Recommends using consumption tax revenues to eliminate the budget defecit, finance Medicare, and eliminate federal excise taxes.